1998
DOI: 10.1101/gad.12.11.1691
|View full text |Cite
|
Sign up to set email alerts
|

Multistep signaling requirements for pituitary organogenesis in vivo

Abstract: During development of the mammalian pituitary gland specific hormone-producing cell types, critical in maintaining homeostasis, emerge in a spatially and temporally specific fashion from an ectodermal primordium. We have investigated the molecular basis of generating diverse pituitary cell phenotypes from a common precursor, providing in vivo and in vitro evidence that their development involves three sequential phases of signaling events and the action of a gradient at an ectodermal boundary. In the first pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
495
2
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(514 citation statements)
references
References 64 publications
13
495
2
4
Order By: Relevance
“…In addition, there is some, although less striking dorso-ventral polarity of the zebrafish adenohypophysis. For instance, gonadotropes are preferentially located ventral of thryrotropes and somatotropes M a n u s c r i p t 7 of the posterior PD (Glasgow et al, 1997, Nica et al, 2004, consistent with the ventral location of gonadotropes in Rathke's pouch, the AH anlage of the mouse ( (Treier et al, 1998, Zhu et al, 2005, Zhu et al, 2007. While the arrangement of PD in anterior and PI in posterior regions of the AH is conserved between zebrafish and mouse, the mouse PD per se does not display an apparent intrinsic anterior-posterior, but rather a dorso-ventral polarity (Treier et al, 1998, Zhu et al, 2005.…”
Section: Ontogeny Of the Zebrafish Adenohypophysissupporting
confidence: 59%
See 2 more Smart Citations
“…In addition, there is some, although less striking dorso-ventral polarity of the zebrafish adenohypophysis. For instance, gonadotropes are preferentially located ventral of thryrotropes and somatotropes M a n u s c r i p t 7 of the posterior PD (Glasgow et al, 1997, Nica et al, 2004, consistent with the ventral location of gonadotropes in Rathke's pouch, the AH anlage of the mouse ( (Treier et al, 1998, Zhu et al, 2005, Zhu et al, 2007. While the arrangement of PD in anterior and PI in posterior regions of the AH is conserved between zebrafish and mouse, the mouse PD per se does not display an apparent intrinsic anterior-posterior, but rather a dorso-ventral polarity (Treier et al, 1998, Zhu et al, 2005.…”
Section: Ontogeny Of the Zebrafish Adenohypophysissupporting
confidence: 59%
“…In mouse pituitary organogenesis, Shh secreted by the oral ectoderm and ventral cells of Rathke's pouch itself acts as a morphogen on the pouch where it promotes the differentiation of ventral cell fates and positively controls proliferation of pituitary precursors (Treier et al, 1998, Treier et al, 2001. A recent study by Guner and colleagues showed that Hh patterns the early zebrafish pituitary placode along its anterior-posterior axis, with highest signaling levels promoting anterior fates .…”
Section: Shhmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the BPES phenotype, FoxL2 is expressed in ovarian follicles and the developing eyelid (53). FoxL2 (initially named PFrk) is also present in the developing pituitary around e10 -10.5 (55). Moreover, FoxL2 expression persists in the adult pituitary and localizes mostly to cells positive for the glycoprotein ␣ subunit (␣GSU) shared by LH, FSH, and thyroid-stimulating hormone (TSH) (56).…”
Section: Foxl2 Is Present In ␣Gsu-and Fsh␤-positive Pituitary Cells-mentioning
confidence: 70%
“…It has been demonstrated that direct contact of the ventral diencephalons with Rathke's pouch is required for pituitary organogenesis and that pituitary cell type determination occurs in response to a series of extrinsic and intrinsic signaling molecules (2)(3)(4).…”
mentioning
confidence: 99%